Jobs and Intimate Partner Violence - Evidence from a Field Experiment in Ethiopia - Andreas Kotsadam; Espen Villanger (Center for Economic Studies and ifo Institute (CESifo), 2020)
We identify the effects of employment on Intimate Partner Violence (IPV) by collaborating with 27 large companies in Ethiopia to randomly assign jobs to equally qualified female applicants. The job offers increase formal employment, earnings, and earnings shares within couples in the short and medium run but we can reject relatively small effects in any direction on our main outcome, physical IPV. In the short run, job offers reduce emotional abuse and there are indications of heterogeneous effects whereby women with low bargaining power at baseline experience increased risks of abuse if offered a job.
Keywords: J20; O10; Z10; 330; employment; gender; RCT; IPV; violence Ethiopia